Commentary and authority in Mesopotamia and Qumran - Brown-deVost, Bronson (Journal of ancient Judaism, 2019)
How did the written word serve as an authoritative source in the ancient world? What does it mean that some works became so popular as to merit dedicated interpretive commentaries? And does any direct relationship exist between the various methods of interpretation and styles of composition in these commentaries? The present work sets out to provide some solid answers to such questions.At the heart of this book stands a comparative analysis of ancient cuneiform commentary texts from mid-to-late first millennium Mesopotamia and early Jewish commentaries—known as pesharim—from the turn of the common era found in caves near Khirbet Qumran. Though some aspects of Mesopotamian hermeneutics may have influenced Jewish exegesis, likely through Jewish Aramaic scribes, the actual Mesopotamian practice of composing commentary texts exerted little-to-no influence on the compositional techniques of the pesharim. Nevertheless, many textual difficulties in the Qumran pesharim can be explained as the result of an accretion of interpretations over an extended period of time—a practice detailed in the textual record of the Mesopotamian commentaries. What is more, these commentaries reveal important evidence about both the way in which and the extent to which such works functioned as authoritative sources. As a result, this book advocates a shift away from discussing textual authority in simple binary terms, both in ancient and modern contexts, to functional descriptions of literary authority.